Vapor‐ and liquid‐phase adsorption of alcohol and water in silicalite‐1 synthesized in fluoride media. Issue 4 (6th January 2020) - DeJaco, Robert F.; Dorneles de Mello, Matheus; Nguyen, Huong Giang T.; Jeon, Mi Young; van Zee, Roger D.; Tsapatsis, Michael; Siepmann, Joern Ilja
Abstract: In this work, batch‐adsorption experiments and molecular simulations are employed to probe the adsorption of binary mixtures containing ethanol or a linear alkane‐1, n ‐diol solvated in water or ethanol onto silicalite‐1. Since the batch‐adsorption experiments require an additional relationship to determine the amount of solute (and solvent) adsorbed, as only the bulk liquid reservoir can be probed directly, molecular simulations are used to provide a relationship between solute and solvent adsorption for input to the experimental bulk measurements. The combination of bulk experimental measurements and simulated solute–solvent relationship yields solvent and solute loadings that are self‐consistent with simulation alone, and allow for an assessment of the various assumptions made in the literature. At low solution concentrations, the solute loading calculated is independent of the assumption made. At high concentrations, a negligent choice of assumption can lead to systematic overestimation or underestimation of calculated solute loading.